International Comparative Human Resource Management Based on the Example of Employee Training in Poland - Kleczewska, Natalia; Ławrynowicz , Maciej (Studia Oeconomica Posnaniensia, 2014)
In this paper we present one of the first comparative human resource management studies in Poland in the field of employee training. In particular, the aim of our study is to identify the variables that affect the practice of training in Poland. In our investigation we rely on two well-established concepts: comparative and contingency theories, using regression analysis to verify the results. A secondary aim of our inquiry is to add certain arguments to the debate concerning the universalistic versus the contingency approach to human resource management in Poland.